The ecological risk of acid mine drainage in a salinising landscape - Vellemu, Emmanuel Captain (Rhodes University, Faculty of Science, Institute for Water Research, 2018)
Acid mine drainage (AMD) and increasing salinity of freshwater ecosystems pose serious threats to water quality in water-stressed South Africa. These threats are exacerbated by mining activities, mainly gold and coal from both active and abandoned mines that continue to release acidic water that is rich in toxic metals and high sulphate concentrations. Therefore, the overarching hypothesis for this study was that "the combination of AMD and sulphate salts confers high ecological risk to the aquatic biota" . The study employed both laboratory and field investigations to test this hypothesis and provide appropriate tools to protect freshwater ecosystems from increasing anthropogenic impacts. Firstly, a laboratory investigation was carried out to develop risk-based water quality guidelines (WQGs) for sulphates and treated AMD (TAMD) using the species sensitivity distributions (SSDs) technique. Five South African freshwater species belonging to five different taxonomic groupings, including Adenophlebia auriculata (insect), Burnupia stenochorias (mollusc), Caridina nilotica (crustacea), Pseudokirchneriella subcapitata (algae) and Oreochromis mossambicus (fish) were exposed to varying concentrations of sodium sulphate (Na2SO4), magnesium sulphate (MgSO4) and calcium sulphate (CaSO4), as well as TAMD in separate ecotoxicological experiments, applying short-term (96 h) non-renewal and long-term (240 h) renewal exposure test methods. Secondly, a novel trait-based approach (TBA) was also used to predict the vulnerability of taxa to treated acid mine drainage (TAMD). The TBA used a combination of carefully selected traits of organisms that are mechanistically linked to TAMD for their potential vulnerability predictions. Leptoceridae (caddisflies) and Leptophlebiidae (mayflies) were selected taxa for evaluation of the trait-based vulnerability predictions to TAMD for laboratory toxicity exposures. This was followed by a field investigation to assess macroinvertebrates assemblage responses, abundance and richness to a TAMD-impacted stream using the South African Scoring System version 5 (SASS5) protocol. Outcomes form the above three sources were combined in a multi-criteria analysis (MCA) to develop an appropriate water quality management strategy in a form of a trait-based decision-making support tool. Results of the risk-based WQGs revealed that Na2SO4 was the most toxic of the tested salts. A concentration of 0.020 g/L Na2SO4, 0.055 g/L CaSO4, and 0.108 g/L MgSO4 or a combined sulphate salts limit of 0.067 g/L were derived as long-term WQGs to protect over 95% of the population species in a natural environment considered as relatively pristine. This means that the generic 0.25 g/L sulphate compliance limit for South African freshwater systems is under-protective. Burnupia stenochorias was the most sensitive to AMD after long-term exposures, and it was adjudged as a good indicator of AMD along with P. subcapitata. Long-term scenario-specific WQG for AMD for the protection of over 95% of the population species was derived as 0.014%. Results of the TBA revealed that the relative abundance and diversity of taxa at a site that received direct impact from TAMD generally corresponded to trait-based predictions. The site that received direct TAMD was largely dominated by members of the Corixidae and Naucoridae families. However, Leptoceridae was more vulnerable to TAMD than Leptophlebidae contrary to predictions. Its assemblage did not match the predictions although Leptophlebiidae corresponded to predictions in terms of its assemblage and diversity. As water quality improved further downstream of the TAMD source, macroinvertebrates assemblage and diversity also improved as predicted. However, it is important to note that other equally important traits that were not studied might influence the response of organisms during toxicity test exposures. The MCA findings suggest that the trait-based decision-making support tool is a useful management strategy for the predicting vulnerability of taxa aquatic stressors including AMD and increasing salinity. Overall, the outcome of this study suggests that AMD poses an ecological risk to aquatic biota, but this becomes riskier in the presence of excess sulphate salts. Albeit, the WQGs for sulphate salts and AMD as well as the developed trait-based decision support tool all contribute novel sound scientific knowledge basis for managing the AMD and increasing salinity in freshwater ecosystems. The study recommends incorporating different life stages of indigenous species tested to determine if their sensitivity to AMD and sulphate would correspond to current findings because early life stages could be more sensitive to aquatic stressors than juveniles or adults. This is important for the derivation of strong and relevant WQGs. The TBA requires further refinement for its incorporation in ecotoxicology on a wide scale.
Keywords: Acid mine drainage Environmental aspects -- South Africa Mpumalanga; Salinization -- South Africa Mpumalanga; Water salinization -- South Africa Mpumalanga; Water quality -- South Africa Mpumalanga; Aquatic animals Effect of water quality on -- South Africa Mpumalanga; Freshwater ecology -- South Africa Mpumalanga